ASSESSMENT OF FOOD SELF-SUFFICIENCY AND STABILITY BASED ON POTENTIAL THEORY - Pershukevich, Petr Mikhailovich; Vasilievna Tyu, Lyudmila; Pavlovich Zadkov, Alexander; Vasilievna Shchetinina, Irina; Mikhailovna Edrenkina, Nina (Revista Inclusiones, 2020)
The paper analyses the food self-sufficiency of Siberia and its stability. The components of the consumer basket are established first. Next, economic and physical access to food is considered. Food availability is analysed further. Food self-sufficiency is determined next. The proposed methodology is applied to assess the level of food self-sufficiency for Siberia. Self-sufficiency is established for grain, potatoes, meat and eggs, though not for milk, vegetables, sugar beet, oilseeds, fish, fruit, salt, spices or tea. The methodology developed by N. V. Shalanov is used to calculate the integral index of stability of agricultural production development in Siberia. The analysis performed indicates that stability is maintained in the main components of agricultural production in Siberia. Meanwhile, the average level of economic development is at 93.09, i.e., corresponds to 93.09% of the reference value.